Dielectronic recombination data for dynamic finite-density plasmas VIII. The nitrogen isoelectronic sequence - Mitnik, D.M. (2004)
Dielectronic recombination data for nitrogen-like ions forming oxygen-like ions has been calculated as part of the assembly of a level-resolved dielectronic recombination database necessary for the modelling of dynamic finite-density plasmas (Badnell et al. 2003). Dielectronic recombination rate coefficients for a selection of ions from O+ to Xe47+ are presented and the results discussed.